Impact of the monetary policy of the People’s Bank of China on the country’s economic development (Journal of Oriental Studies, 2020)
This article analyzes the current monetary policy of China. The analysis of the monetary policy of the Central Bank of China and the impact of its individual instruments on economic growth will continue. Currently the Central Bank of China conducts an independent monetary policy and uses a number of classic and modern tools to implement it. This has a positive impact on the state of the entire Chinese economy. The author concludes that effective implementation of monetary policy is possible only if there is a stable functioning financial market and public confidence in the state. Direct and indirect methods of China’s monetary policy contribute to economic growth. Direct methods include direct financing of certain projects by the People’s Bank of China, as well as providing loans to commercial banks to Finance certain programs and projects. Indirect methods consist in formulating recommendations, as well as creating conditions for financial institutions involved in financing and investing in priority sectors of the economy. China does not seek to copy global trends in monetary policy, but rather pursues a monetary policy that is focused on the current needs of the economy. The authors conclude that the goals and instruments of the People’s Bank of China are adjusted in accordance with economic conditions. Through the banking system China develops the real sector of the economy, stimulates economic growth pursues a policy of strengthening the national currency and maintains inflation at the level necessary for the sustainable functioning of the economic system. The value of the study is that the conclusions made by the authors expand and define the understanding that monetary policy has a great impact on economic growth. Key words: monetary policy, economic growth, banking system, macroeconomic policy, reform, devaluation.